Relationship between Rewards and Employee Motivation in the Non Profit Organizations of Nepal - Ojha, Aayush; Pradhan, Sumit (Nepalese Journal of Business, 2025)
This study examines the relationship between rewards and employee motivation in the non-profit organizations of Nepal. Employee motivation is the dependent variable. The selected independent variables are career growth opportunities, challenging tasks, recognition and awards, fringe benefits, and promotion. The primary source of data is used to assess the opinions of respondents regarding career growth opportunities, challenging tasks, recognition and awards, fringe benefits, promotion, and employee motivation. The study is based on primary data of 130 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of rewards and employee motivation in the non-profit organizations of Nepal. The study showed a positive impact of career growth opportunities on employee motivation. It indicates that satisfactory career growth opportunities lead to increase in employee motivation. Similarly, the study showed a positive impact of challenging tasks on employee motivation. It indicates that h higher the level of challenging tasks, higher would be the employee motivation. Likewise, the study also revealed a positive impact of recognition and awards on employee motivation. It indicates that employee who get recognized and are award are highly motivated to perform their job. Further, the study observed a positive impact of fringe benefits on employee motivation. It indicates that better fringe benefits attract the employees to be more motivated towards their job. In addition, the study observed a positive impact of promotion on employee motivation. It indicates that higher the opportunities of promotion, higher would be the employee motivation.